Statistical profile of immigrant users of women’s shelters in Andalusia, Spain - Toledo-Larrea, Juana de los Ángeles; Sánchez-Rodríguez, María Isabel (Convergencia Revista de Ciencias Sociales, 2019)
in Spain the twenty-first century began with important modifications to the law on immigration (Organic Law 4/2000) and relating to gender-based violence (Organic Law 1/2004). These simultaneous modifications to these laws prompted this study, whose aim is the determination of the profile and socioeconomic achievements of immigrant women victims of gender-based violence after being admitted in an Andalusian women’s shelter. The statistical work includes data on immigrant users of shelters that were collected in the framework of a research project, as well as official data sources. Some of the main conclusions are that the majority of these women have a family history of abuse and are derivative victims of abuse, filed police reports and protection orders obtained against the perpetrators and the economic resources of these women after leaving the shelter is a significant factor in their decision to return to the abuser.